2023
DOI: 10.1177/15589447231174175
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Dupuytren Disease: A Systematic Review and Network Meta-analyses

Abstract: Background: Dupuytren disease is a common fibroproliferative disease that affects the palmar fascia of the hands. Currently, there is limited consensus regarding the optimal therapy for this condition, with treatment decisions based largely on surgeon preference. Therefore, the aim of this study was to determine which treatments are the most effective for Dupuytren disease. Method: A systematic review and network meta-analyses were conducted in accordance with the Preferred Reporting Items for Systematic Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…M. Brazzelli et al [11] note that eight years after the use of Clostridium histolyticum collagenase preparations, recurrence is observed in 100% of cases. According to S. Nann et al [18], the highest probability of contracture recurrence is observed between 2 and 5 years after the intervention. In this study, it was not possible to assess the recurrence rate due to the short follow-up period.…”
Section: Discussionmentioning
confidence: 98%
“…M. Brazzelli et al [11] note that eight years after the use of Clostridium histolyticum collagenase preparations, recurrence is observed in 100% of cases. According to S. Nann et al [18], the highest probability of contracture recurrence is observed between 2 and 5 years after the intervention. In this study, it was not possible to assess the recurrence rate due to the short follow-up period.…”
Section: Discussionmentioning
confidence: 98%